Successful Balloon-Expandable Transcatheter Aortic Valve Replacement for Extremely Large Annulus (>1,000 mm2) - Tadatomo Fukushima, MD; Kenichi Ishizu, MD; Akihiro Isotani, MD; Shinichi Shirai, MD; Kenji Ando, MD (JACC: Case Reports, 2024)
Transcatheter aortic valve replacement in extra-large annulus is challenging because of the limited sizes and data of the current commercial prosthesis sizes available. We present a case of successful transcatheter aortic valve replacement with a new balloon-expandable SAPIEN 3 Ultra RESILIA valve for an aortic annulus area >1,000 mm2 on computed tomography.